Recipient Selection for Optimal Utilization of Discarded Grafts in Liver Transplantation. Issue 5 (May 2018) - Giretti, Giovanni; Barbier, Louise; Bucur, Petru; Marques, Frédéric; Perarnau, Jean-Marc; Ferrandière, Martine; Tellier, Anne-Charlotte; Kerouredan, Vincent; Altieri, Mario; Causse, Xavier; Debette-Gratien, Maryline; Silvain, Christine; et al.
Abstract : Background: In France, liver grafts that have been refused by at least 5 teams are considered for rescue allocation (RA), with the choice of the recipient being at the team's discretion. Although this system permits the use of otherwise discarded grafts in a context of organ shortage, outcomes and potential benefits need to be assessed. Methods: Between 2011 and 2015, outcomes of RA grafts (n = 33) were compared with SA grafts (n = 321) at a single French center. Results: Liver grafts in the RA group were older (63 ± 17 years vs 54 ± 18 years, P = 0.007) and had a higher DRI (1.86 ± 0.45 vs 1.61 ± 0.47, P = 0.010). Recipients in this group had a lower Model for End-Stage Liver Disease score (14 ± 5 vs 22 ± 10, P < 0.001) and had mostly hepatocellular carcinoma (67.0% vs 40.4%, P = 0.010). The balance of risk score was significantly lower in the RA group (5.5 ± 2.9 vs 9.2 ± 5.5, P < 0.001). There were higher rates of early and delayed hepatic artery thrombosis (15.2% vs 3.1%, P = 0.001) and retransplantation (18.2% vs 4.7%, P = 0.002) in the RA group. Patient survival was not different between groups, but graft survival was impaired (95% vs 82% at 1 year and 94% vs 74% at 3 years, P = 0.001). Conclusion: Our results show that discarded liver grafts can be used provided that there is a strict recipient selection process, although hepatic artery thrombosis and retransplantation are more frequent. This strategy enables utilization of otherwise discarded grafts in the context of organ shortage. Abstract : In the French liver allocation system, grafts that are refused by 5 centers are available for use at the discretion of the center termed rescue allocation. In the authors' experience, these grafts are used with comparable patient survival but an increased risk of hepatic artery thrombosis and retransplantation. Strategies for improved outcomes are discussed. Supplemental digital content is available in the text.